Development of the Chinese coaches’ autonomy-supportive—laissez-faire coaching style scale - Su, Wen; Wang, Liqin; Ding, Yingmin; Zhao, Daliang (Frontiers in Psychology, 2024)
The autonomy-supportive coaching style is recognized for its positive impact on athletes' well-being and performance. However, the transition of excessive autonomy into a laissezfaire coaching style has not been thoroughly examined within the context of coach evaluation scales. Existing scales focus predominantly on the positive dimensions of autonomy support, and do not possess the capabilities to measure outcomes which may be viewed as negative or other outcomes. This study aims to integrate the autonomy-supportive and laissez-faire coaching styles within the same measurement framework. Methods: Our study developed a comprehensive scale to assess both the autonomy-supportive and laissez-faire coaching styles, drawing on items from the Sport Climate Questionnaire for autonomy support and adapting items from leadership research for laissez-faire coaching. We conducted two studies: the first with 148 athletes to refine the laissez-faire items and the second with 460 athletes to validate the full scale, utilizing exploratory factor analysis, confirmatory factor analysis, and correlation analysis. We also measured internal consistency and split-half reliability. Results: The finalized scale includes a 6-item autonomy-supportive subscale and a 5-item laissez-faire subscale. Validation processes confirmed the scale's construct and criterion validity, alongside its reliability. Discussion: The Chinese Coaches' Autonomy-Supportive -Laissez-Faire Coaching Style Scale effectively captures both the beneficial and potentially detrimental aspects of coaching styles, addressing a critical gap in the literature and providing a reliable tool for evaluating coaching approaches.